Photoluminescent Lanthanide-Doped Silica Nanotubes: Sol−Gel Transcription from Functional Template - Qiao, Yan; Chen, Huanfa; Lin, Yiyang; Yang, Zhiyi; Cheng, Xinhao; Huang, Jianbin (Journal of physical chemistry. C, 2011)
Functional photoluminescent materials have emerged as a fascinating research subject holding great promise in versatile applications. In this report, photoluminescent lanthanide-organic hybrid nanofibers in hydrogels are fabricated through supramolecular self-assembly, which can serve as functional soft templates to prepare inorganic nanomaterials. By using sol−gel transcription of tetraethylorthosilicate (TEOS), novel lanthanide-doped silica nanotubes are conveniently prepared, in which lanthanide ions are embedded into the silica nanotube walls. In this approach, luminescent lanthanide ions transfer from organic nanofibers into inorganic silica nanotubes. Moreover, different kinds of lanthanide-doped silica nanotubes with tunable photoluminescent emission color can be achieved by changing the doping ions such as Tb3+ and co-doping Tb3+/Eu3+ in the soft template. The lanthanide-doped silica nanotubes are potentially used as nanostructured optical devices and sensors.